: “Alguém sabe o que é isso?”: o gerenciamento de posturas epistêmicas na ativação de conhecimento prévio. - Mascarenhas, Igor Jose Souza (2020)
This research aims to investigate which interactive resources are mobilized in the activation phase of previous knowledge in English class as an additional language for a class of 5th grade in a public school in Greater Vitória, whose students are betwee